A Model of IT Evaluation Management: Organizational Characteristics, IT Evaluation Methodologies, and B2BEC Benefits - Lin, Chad; Huang, Y. (Springer-Verlag, 2007)
Large organizations have invested substantial financial resources ininformation technology (IT) over the last few decades. However, many organizationshave discovered that they have not yet fully reaped the B2BEC benefits from their IT investments. A model of IT evaluation management is proposed in this paper to examine: (1) the relationship between the adoption of ITEM and B2BEC benefits; and (2) the impact of organizational characteristics (e.g. organizational IT maturity and IT evaluation resources (ITER) allocation) on the relationship between the adoption of ITEM and B2BEC benefits. The cross national survey results provide empirical evidence in support of our proposed model, and demonstrate that: (a) the level of organizational IT maturity has a direct and significant impact on the adoption of ITEM; (b) the adoption of ITEM has a positive relationship with the ITER allocation; and (c) the ITER allocation has a significant direct influence on B2BEC benefits.